Research on damage and degradation of coal-bearing sandstone under freeze-thaw cycles - Mao, Yiwen; Li, Ming; Wu, Peng; Guo, Shuai; Zhu, Fuqiang (Frontiers in Earth Science, 2025)
Comprehending the effect of freeze-thaw cycles on the damage and degradation of coal-bearing sandstones is crucial for the end-wall slope stability of open-pit mines in cold areas. In this study, freeze-thaw cycle tests on water-saturated coal-bearing sandstone samples under different freezing temperatures and different freeze-thaw cycles were conducted by a fully automatic low-temperature freeze-thaw testing system, and the effects of freeze-thaw cycle parameters on P-wave velocity and porosity of sandstone samples were obtained. With the assistance of CT scanning imaging technology, the microscopic damage and deterioration mechanism of sandstone samples under freeze-thaw cycles was further revealed, and a characterization method for the damage and deterioration of sandstone samples under freeze-thaw cycles was established, and damage and degradation effects of freeze-thaw cycles on the sandstone samples were predicted. The research results suggest that as the freezing temperature decreases and the number of freeze-thaw cycles increases, the P-wave velocity of the sandstone sample decreases, while the volume of the sandstone sample increases. The relative change rate of P-wave velocity and porosity increment of the sample are positively correlated with freezing temperature, and negatively correlated with the number of freeze-thaw cycles. The CT scan results show that with the decrease of the freezing temperature and the increase of the number of freeze-thaw cycles, the number and geometric size of pores on the sample cross section increase significantly. Additionally, the evolution equation of freeze-thaw damage factors was established with freezing temperature and number of freeze-thaw cycles as parameters, and the internal mechanism and physical characterization of freeze-thaw damage degradation of coal measure sandstone were revealed. This research provides a reference for the safety and stability evaluation and technology research and development of related rock engineering in cold areas.